THE ROLE OF CBCT IN ASSESSING THE SEVERITY OF WISDOM TEETH INCLUSION COMPARED TO CONVENTIONAL RADIOLOGICAL TECHNIQUES - Dorin Ioan Cocoș; Mariana Păcurar; Andreea Claudia Nistor; Doina Moaleș; Izabela Diana Cocoș; Kamel Earar (Romanian Society of Oral Rehabilitation, 2024)
CBCT (Cone Beam Computed Tomography) is a medical imaging technique that provides three-dimensional images of anatomical structures. In dentistry, CBCT has proven to be particularly useful for evaluating included teeth, including wisdom teeth, as opposed to conventional dental X-rays, which provide only two-dimensional images. Thanks to CBCT, the relationships between the included teeth and other structures, such as neighboring roots, nerves, blood vessels, and soft tissues, can be assessed. This information is crucial to prevent accidental damage to these structures during surgery. It also offers the possibility to determine the most appropriate direction for the extraction of the included teeth, thus minimizing trauma to adjacent tissues and accelerating the postoperative recovery process. Thanks to the detailed information provided, a personalized treatment plan can be created for each patient, adapted to the anatomical particularities of each case. The choice between CBCT and conventional radiological techniques depends on the specific clinical needs of each case. In situations where it is necessary to accurately achieve precise three-dimensional details com chooses to perform CBCT, in cases where a general panoramic image is sufficient and the need for details is not so demanding because the operative techniques are not subject to operative or postoperative accidents we will opt for conventional radiological techniques because it may be a more suitable option, also considering the much lower radiation dose.